Dexamethasone Pretreatment Alleviates Isoniazid/Lipopolysaccharide Hepatotoxicity: Inhibition of Inflammatory and Oxidative Stress - Hassan, Hozeifa M.; Guo, Hongli; Yousef, Bashir A.; Ping-Ping, Ding; Zhang, Luyong; Jiang, Zhenzhou (Frontiers in Pharmacology, 2017)
Isoniazid (INH) remains a cornerstone key constitute of the current tuberculosis management strategy, but its hepatotoxic potentiality remains a significant clinical problem. Our previous findings succeed to establish a rat model of INH hepatotoxicity employing the inflammatory stress theory in which non-injurious doses of inflammatory-mediating agent bacterial lipopolysaccharides (LPS) augmented the toxicity of INH that assist to uncover the mechanisms behind INH hepatotoxicity. Following LPS exposure, several inflammatory cells are activated and it is likely that the consequences of this activation rather than direct hepatocellular effects of LPS underlie the ability of LPS to augment toxic responses. In this study we investigated the potential protective role of the anti-inflammatory agent dexamethasone (DEX), a potent synthetic glucocorticoid, in INH/LPS hepatotoxic rat model. DEX pre-treatment successfully eliminates the components of the inflammatory stress as shown through analysis of blood biochemistry and liver histopathology. DEX potentiated hepatic anti-oxidant mechanisms while serum and hepatic lipid profiles were reduced. However, DEX administration was not able to revoke the principal effects of CYP2E1 in INH/LPS-induced liver damage. In conclusion, this study illustrated the DEX-preventive capabilities on INH/LPS-induced hepatotoxicity model through DEX-induced potent anti-inflammatory activity whereas the partial toxicity seen in the model could be attributed to the expression of hepatic CYP2E1. These findings potentiate the clinical applications of DEX co-administration with INH therapy in order to reduce the potential incidences of hepatotoxicity.